2017
DOI: 10.1016/j.jegh.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

‘Before reaching the last mile’- Knowledge, attitude, practice and perceived barriers related to tuberculosis directly observed therapy among ASHA workers in Central India: A mixed method study

Abstract: Study revealed inadequate knowledge and unsatisfactory practice related to DOT provision among ASHAs. Innovations addressing the perceived barriers to improve practice of DOT provision by ASHAs are urgently required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 22 publications
0
37
1
Order By: Relevance
“…Empirical evidence linking knowledge to service delivery and performance is emerging, but limited [11]. In India, assessments of ASHA knowledge have been small in scale and often constrained to a single topical area, including oral health [12], tuberculosis [13], and diarrhea [14]. Broader assessments of ASHA's RMNCH&N knowledge and practices have pointed to significant gaps in knowledge about pre-eclampsia etiology [15], promotion of institutional delivery contraceptive-use [16], obstetric danger sign assessment [17], and neonatal care [18].…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence linking knowledge to service delivery and performance is emerging, but limited [11]. In India, assessments of ASHA knowledge have been small in scale and often constrained to a single topical area, including oral health [12], tuberculosis [13], and diarrhea [14]. Broader assessments of ASHA's RMNCH&N knowledge and practices have pointed to significant gaps in knowledge about pre-eclampsia etiology [15], promotion of institutional delivery contraceptive-use [16], obstetric danger sign assessment [17], and neonatal care [18].…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 11 ] In our study, most of the ASHAs were in the age range of 31–40 years, with the mean age being 35.82 ± 8.62 years, while other studies reported variable age groups like 29.55, 41 etc. [ 12 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other countries that verified the knowledge of health workers point to gaps in practice and knowledge related to DOT, indicating urgency in adopting innovations that address perceived barriers and improve the knowledge of professionals involved in the practice [18][19][20] . One of the main focus of discussion in the study by Choowong et al 20 addresses the need for professionals who are able to 24) 9 ( 7) 10 ( 7) 5 ( 4)…”
Section: Discussionmentioning
confidence: 99%